Application of bioelectrochemical systems in wastewater treatment and hydrogen production - Krishnan, Santhana; Kadier, Abudukeremu; Mohd Fadhil, Md Din; Mohd, Nasrullah; Nurul Nazleatul, Najiha; Shazwin, Mat Taib; Zularisam, Ab Wahid; Li, Yu You; Qin, Yu; Pant, Kamal Kishore; Chelliapan, Shreeshivadasan; Kamyab, Hesam R.; et al. (Elsevier, 2020)
As a renewable energy carrier, hydrogen gains international recognition, with the ability to substitute fossil fuels. A state-of-the-art technology called a microbial electrolysis cell (MEC) can produce viable, clean hydrogen energy and also treat wastewater using various renewable carbon sources. The key substrates tested include wastewater, fermentable, and nonfermentable organic effluents. This chapter mainly discuss the scientific fundamentals of MEC technology, including its operating principles, thermodynamics, and electron transfer mechanisms. This chapter also discusses the nutrient, heavy metal removal, and integrated technologies used for higher hydrogen production